2021
DOI: 10.7150/thno.57511
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism-mediated targeting hyperthermia-immunotherapy in “cold” tumor with CSF1R inhibitor

Abstract: Background: Immunotherapy has profoundly changed the landscape of cancer management and represented the most significant breakthrough. Yet, it is a formidable challenge that the majority of cancers - the so-called “cold” tumors - poorly respond to immunotherapy. To find a general immunoregulatory modality that can be applied to a broad spectrum of cancers is an urgent need. Methods: Magnetic hyperthermia (MHT) possesses promise in cancer therapy. We develop a safe and effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…[10] The main benefit of MHT relates to its ability to treat site-specific cancer whilst avoiding hazardous systemic effects. [11] Furthermore, MHT is minimally invasive (i.e., delivered intratumorally or intravenously by injection), with mild side effects compared to radiotherapy or chemotherapy, [10] and shows synergistic effects with many cancer treatments, e.g., brachytherapy, [12] drug-delivery, [13] immunotherapy, [14] and gene therapy. [15] Highly porous, ferromagnetic glass-ceramic P40-Fe 3 O 4 microspheres (125-212 µm) with enhanced cytocompatibility have been manufactured for the first time via a facile, rapid, single-stage flame spheroidization process.…”
Section: Ferromagnetic Cytocompatible Glass-ceramic Porous Microspher...mentioning
confidence: 99%
“…[10] The main benefit of MHT relates to its ability to treat site-specific cancer whilst avoiding hazardous systemic effects. [11] Furthermore, MHT is minimally invasive (i.e., delivered intratumorally or intravenously by injection), with mild side effects compared to radiotherapy or chemotherapy, [10] and shows synergistic effects with many cancer treatments, e.g., brachytherapy, [12] drug-delivery, [13] immunotherapy, [14] and gene therapy. [15] Highly porous, ferromagnetic glass-ceramic P40-Fe 3 O 4 microspheres (125-212 µm) with enhanced cytocompatibility have been manufactured for the first time via a facile, rapid, single-stage flame spheroidization process.…”
Section: Ferromagnetic Cytocompatible Glass-ceramic Porous Microspher...mentioning
confidence: 99%
“…187 For example, the magnetic liposome constructed by Fang et al showed significant magnetic targeting ability and could be effectively accumulated in tumor sites under the action of an external magnetic field. 188 Meanwhile, as a stimulus with no tissue depth limitation, a magnetic field can also precisely regulate drug release from deep diseases without causing significant side effects to surrounding healthy tissues. For instance, a transferrin-conjugated doxorubicin-encapsulated magnetic nanoplatform could effectively release the drug in brain tumors under an external magnetic field.…”
Section: Mins-based Strategies In Therapy and Imagingmentioning
confidence: 99%
“…For external stimuli, hyperthermia can be utilized as a physical stimulus for antitumor therapeutic response of NPs. There was a study about magnetic hyperthermia, namely that a liposome loaded with superparamagnetic NPs and CSF1R inhibitor BLZ945 were constructed for antitumor immune response under magnetic hyperthermia responses 138 . Photo, identified as a common physical responsiveness, are usually applied for some inorganic NPs with optical/electronic properties, including AuNRs/NPs, Fe 3 O 4 NPs, BP NPs, etc.…”
Section: Rational Design Of Tams-focused Functional Nanomedicinesmentioning
confidence: 99%